Observation based control model approximation through fuzzy-genetic learning - Foo, Tee Jong. (2008)
An approach for control model approximation using fuzzy-genetic learning techniques is considered in this report. The focus will be on the hardware setup for capturing and recording scenes of the control session. Subsequently, the software aspect of data processing required to filter the signals recorded to derive the necessary samples to be used in the approximation of the control model using the fuzzy-genetic learning technique. Based on the observations, the learning module is able to derive an n-rule fuzzy control system for the problem in consideration.